Bilirubin Inhibits Neointima Formation and Vascular Smooth Muscle Cell Proliferation and Migration - Peyton, Kelly J.; Shebib, Ahmad R.; Azam, Mohammad A.; Liu, Xiao-ming; Tulis, David A.; Durante, William (Frontiers in Pharmacology, 2012)
Bilirubin is a heme metabolite generated by the concerted action of the enzymes heme oxygenase and biliverdin reductase. Although long considered a toxic byproduct of heme catabolism, recent preclinical, and clinical studies indicate the bilirubin exerts beneficial effects in the circulation. In the present study, we determined whether local administration of bilirubin attenuates neointima formation following injury of rat carotid arteries. In addition, the ability of bilirubin to regulate the proliferation and migration of human arterial smooth muscle cells (SMCs) was investigated. Local perivascular administration of bilirubin immediately following balloon injury of rat carotid arteries significantly attenuated neointima formation. Bilirubin-mediated inhibition of neointimal thickening was associated with a significant decrease in ERK activity and cyclin D1 and A protein expression, and an increase in p21 and p53 protein expression in injured blood vessels. Treatment of human aortic SMCs with bilirubin inhibited proliferation and migration in a concentration-dependent manner without affecting cell viability. In addition, bilirubin resulted in a concentration-dependent increase in the percentage of cells in the G0/G1 phase of the cell cycle and this was paralleled by a decrease in the fraction of cells in the S and G2M phases of the cell cycle. Finally, bilirubin had no effect on mitochondrial function and ATP content of vascular SMCs. In conclusion, these studies demonstrate that bilirubin inhibits neointima formation after arterial injury and this is associated with alterations in the expression of cell cycle regulatory proteins. Furthermore, bilirubin blocks proliferation and migration of human arterial SMCs and arrests SMCs in the G0/G1 phase of the cell cycle. Bilirubin represents an attractive therapeutic agent in treating occlusive vascular disease.